La postura dell’esule: Walter Benjamin e Bertolt Brecht a confronto - Muroni, Giulia (Mimesis Journal, 2024)
The relationship between the philosopher Walter Benjamin and the playwright Bertolt Brecht opens to original theoretical implications. This paper highlights some of them, bound to the artwork and the role of the intellectual. Following a chronological line, it depicts the idea that this encounter had been extraordinary and misunderstood both from the Institut für Sozialforschung and the Jew Academic School, represented by Gershom Scholem.